STIMULUS–ORGANISM–RESPONSE (SOR) APPROACH IN ANALYZING THE EFFECT OF LIVE STREAMING TYPES ON TRUST, IMPULSIVENESS, AND PURCHASE INTENTION OF E-COMMERCE CONSUMERS - Ambar Wulan Sari; Yolanda Masnita; Kurniawati (Majapahit Journal of Islamic Finance and Management, 2026)
This study was designed to analyze the influence of various live streamer types on consumer purchase intentions, while also examining the role of trust and impulsive buying behavior as mediating variables in the context of live streaming commerce (LSC). A quantitative descriptive survey approach was used, collecting data from 200 LSC user respondents using a structured questionnaire. The data obtained were then analyzed using Structural Equation Modeling (SEM) with AMOS, including testing the validity and reliability of the instrument, evaluating the model's feasibility, and analyzing the direct and indirect effects between variables. The study's findings indicate that live streamer type contributes positively and significantly to the level of trust and impulsive buying tendencies, which in turn also have a significant impact on increasing purchase intentions. Furthermore, trust and impulsive buying are proven to function as mediators in this relationship, with the indirect effect being more dominant than the direct effect. The novelty of this study lies in the simultaneous testing of these two psychological variables as mediating mechanisms in the structural model, specifically in the context of LSC in Indonesia. Practically and theoretically, the results of this study contribute to the development of social commerce studies, particularly in helping businesses and e-commerce platforms optimize their live streaming strategies by increasing the credibility, interactivity, and quality of communication displayed by live streamers.